Earth Empire and Sacred Text: Muslims and Christians as Trustees of Creation by David L. Johnston (London and Oakville, CT: Equinox Publishing, Ltd., 2010, hbk. 641 pages) (American Journal of Islam and Society, 2011)
There is a new trend in the progressive quarter of American EvangelicalChristianity to form common bonds with Muslims. From this impulsestem books such as Miroslav Volf’s Allah: A Christian Responseand Carl Medearis’ Muslims, Christians, and Jesus: Gaining Understandingand Building Relationships, as well as organizations such as RickLove’s Peace Catalyst and Yale Divinity School’s Reconciliation Program.David Johnston’s robust Earth, Empire and Sacred Text falls withinthis trend (although these are by no means monolithic attempts and each must be evaluated on its own terms). As an Evangelical Christianwith an academic streak and extensive international experience, Johnstonis uniquely positioned to not only reach out to Muslims but alsoto educate his fellow American Christians. The book is an extraordinaryundertaking and may be considered a three-volume work collapsedinto one. Devout yet pragmatic, Johnston is prepared to engagethe reality of the world in order develop a theology that acknowledgesits own limitations. Johnston combines intellectual rigor with politicalactivism, while remaining theologically inclusive yet authentic ...